The development of women`s professional ice hockey in China: leveraging international competition to change institutionalized gender norms - Li, H.; Nite, C.; Weiller-Abels, K.; Nauright, J. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
This research focused on examining the Chinese professional hockey club in the Canadian Women`s Hockey League, the Chinese national women`s hockey team in the context of an emerging market for hockey, and the Chinese government`s winter sports strategy. We employed a mix of critical feminist theory and the concept of institutionalization to break down the position and aims of women`s hockey development in China. Data were analyzed through content analysis methods. Findings indicated that ice hockey development in China has framed the leveraging strategies for the success of the 2022 Winter Olympics with opportunities and multiple resources, and the government and private actors are trying to reduce the gaps of inequality by providing equal rights, increasing female players` payments, building girls` teams, and making national heroines.